PERAN PEKERJA SOSIAL DALAM PENANGANAN ORANG TERLANTAR DI KOTA PEKANBARU - Hy, Moralely; Bayu Indra Laksana (Prodi Pengembangan Masyarakat Islam STAI Diniyah Pekanbaru, 2024)
Abstract This study aims to analyze the role of social workers in handling displaced people in Pekanbaru City. This type of research is qualitative research, using descriptive methods. Data were collected through interviews. The results of this study indicate that social workers play a role in the Needs Assessment which is carried out at an early stage to assess the physical, mental, and social conditions of displaced people. Social workers play a role in Direct Intervention: Providing emergency assistance such as temporary housing or what is called a shelter, providing food, and health services. Assistance and Counseling in this case social workers provide emotional support and counseling so that they can improve the quality of life of displaced people. and finally social workers act as Social Service Liaisons which connect displaced people with government and private assistance institutions or programs. For example, displaced people are given clothing and food assistance when they are going to their home area and when they arrive in their home area, when displaced people need assistance with economic programs or empowerment, they will be entered into the integrated social welfare data DTSKS so that displaced people can get various assistance. Keywords: The role of Social Workers, Displaced Persons